TriplatinNC and Biomolecules: Building Models Based on Non-covalent Interactions - Rosa, Nathália M. P.; Ferreira, Frederico Henrique do C.; Farrell, Nicholas P.; Costa, Luiz Antônio S. (Frontiers in Chemistry, 2019)
The class of polynuclear platinum(II) compounds have demonstrated a great interest because their high activity against cancer cells. Among these new compounds, the TriplatinNC also called AH78, demonstrated surprising antitumor activity, in some cases equivalent to cisplatin. It is well known that complex charge +8 favors interaction with DNA and other biomolecules non-covalently, through the hydrogen bonds with phosphate and sulfate groups present in these structures. The hydrogen atoms of the amine interact with the oxygen atoms of the phosphate and sulfate groups present in the DNA strand and heparan sulfate, respectively. These interactions can cause significant twists in double helix and inhibit the activity of these biomolecules. The present investigation is an attempt to provide a benchmark theoretical study about TriplatinNC. We have described the non-covalent interactions through small reliable mimetic models. The non-covalent interactions were also evaluated on larger models containing DNA fractions with six nitrogenous base pairs (CGCGAA) and fractions of the disaccharide that makes the HS evaluated by the hybrid QM/MM ONIOM methodology.